Variabilidade genética de Colletotrichum gloeosporioides e Colletotrichum acutatum em seringueira (Hevea brasiliensis) no Brasil - Sierra Hayer, Juan Fernan [UNESP] (2014)
The rubber tree [Hevea brasiliensis (Wild. ex Adr. Than Juss. ) Muell - Arg] is the largest source of natural rubber, widely cultivated, and of great commercial importance due to its high production capacity. Currently the rubber trees are being attacked for various diseases, causing huge economic losses. Among them, the anthracnose, caused by Colletotrichum gloeosporioides and Colletotrichum acutatum, is in all rubber crops places of the world. These fungi causes various damage, such as injuries on leaves, branches, fruits, as well as cankers in the taping panel. Given this situation, and the high incidence of this pathogen in the rubber crop, this study aimed to identify the genetic variability of the isolates of C. gloeosporioides and C. acutatum associated to rubber crop. Phylogenetic and population tools were performed to determine the distribution and frequency of each possible haplotypes. The 79 samples collected in the field were amplified by PCR by specific primers of the ITS spacers regions and the 18S, 28S and 5.8 S genes. Subsequently, the amplified regions were sequenced by the Sanger method. Several sequences available in NCBI were added, to complement the analysis, totaling a data matrix of 263 samples. Phylogenetic analyses generated by Bayesian, Maximum Likelihood and Neighbour -Joining methods, showed the division of the C. acutatum and C. gloeosporioides groups, enabling the separation of the matrix in two specific species. The population analysis showed some very common haplotypes distributed around the world, as well as another haplotypes with very restricted distribution, such as H1 haplotype of ...